(untitled) (Boletín Epidemiológico Semanal, 2025)
Introduction: Outbreaks are a major public health problem. Early outbreak detection and investigation are key to implement the most effective measures. This study aims to describe the non-foodborne outbreaks reported to the Spanish National Surveillance System in the 2018-2022 period. Method: A descriptive study was conducted by disease group and causative agent of non-foodborne outbreaks (excluding healthcare associated infections and COVID-19 outbreaks) between 2018 and 2022. Results: A total of 3,858 outbreaks were reported, with 45,140 associated cases, 2,205 hospitalizations and 181 deaths. The main diseases causing outbreaks were gastrointestinal diseases (n=1,076 outbreaks), followed by vaccine-preventable diseases (n=795) and infestations (scabies and lice) (n=734). The highest number of hospitalizations was due to respiratory diseases and legionellosis (872 and 428, respectively). The number of reported outbreaks decreased in 2020, but a progressive increase was observed from 2021 onwards, approaching the pre-COVID-19 pandemic levels, with important differences depending on the disease. The main exposure setting was the household (1,507 outbreaks), followed by nursing homes (816 outbreaks). The Autonomous Regions did not report outbreaks uniformly during the study period. Discussion: Analysis of the data shows the disruption of epidemiological surveillance caused by the COVID-19 pandemic. Outbreak surveillance helps guide prevention and control measures and it makes possible to assess the epidemiological situation of some diseases for which case-based surveillance is not implemented.